Transcriptional interference perturbs the binding of Sp1 to the HIV-1 promoter. - Greger, I; Demarchi, F; Giacca, M; Proudfoot, N (1998)
Transcriptional interference between adjacent genes has been demonstrated in a variety of biological systems. To study this process in RNA polymerase II (pol II) transcribed genes we have analysed the effect of transcription on tandem HIV-1 promoters integrated into the genome of HeLa cells. We show that transcriptional activation at the upstream promoter reduces transcription from the downstream promoter, as compared with basal transcription conditions (in the absence of an activator). Furthermore, insertion of a strong transcriptional termination element between the two promoters alleviates this transcriptional interference, resulting in elevated levels of transcription from the downstream promoter. Actual protein interactions with the downstream (occluded) promoter were analysed by in vivo footprinting. Binding of Sp1 transcription factors to the occluded promoter was reduced, when compared with the footprint pattern of the promoter protected by the terminator. This suggests that promoter occlusion is due to disruption of certain transcription factors and that it can be blocked by an intervening transcriptional terminator. Chromatin mapping with DNase I indicates that a factor binds to the termination element under both basal and induced conditions.